HEXACO‐60 Personality Trait Inventory: Psychometric characteristics in a sample of medical students from Serbia. Issue 6 (16th September 2021) - Ristic, Ivan; Dotlic, Jelena; Ignjatovic‐Ristic, Dragana; Gazibara, Tatjana
Abstract: The 60‐item HEXACO (HEXACO‐60) Personality Trait Inventory may be strategically more important for researchers compared to the 100‐item HEXACO. The aim of this study was to assess the psychometric properties of the 60‐item HEXACO questionnaire in the Serbian language. This cross‐sectional study, conducted at three of five Faculties of Medicine during the summer semester of the 2016/2017 academic year, included 617 students. Relevant data were collected by an anonymous questionnaire. Cronbach's α and McDonald's ω coefficients for the total scale were .71 and .72, respectively. Apart from Agreeableness, all other domains showed an adequate level of internal consistency (both Cronbach's α and McDonald's ω coefficients were >.70). Random data eigenvalues obtained on the parallel analysis had higher values than initial exploratory factor analysis eigenvalues up to the sixth factor. Accordingly, it was concluded that six factors should be extracted from the Serbian HEXACO‐60. These factors corresponded in item distribution with the original ones. Based on the confirmatory factor analysis, using both 60 items and 24 facets, overall goodness of fit of the Serbian HEXACO‐60 was acceptable. Moreover, there were no domains with completely invalid indices, as there were at least two indices that were acceptable for each domain. The Serbian version of the HEXACO‐60 has acceptable psychometric properties. This shorter version with 60 items may be more suitable for brief surveys or when the time allocated to fill in a questionnaire is limited.